Rejecting Geothermal Projects: Muslim Environmentalism in The SAPAR Movement for Ecological Justice and Sustainable Natural Resources - Muizudin Muizudin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
This study investigates the Syarekat Perjuangan Rakyat Padarincang (SAPAR) movement, which resists a geothermal project on Mount Parakasak, Banten, through the lens of Muslim environmentalism. The project provoked strong opposition due to concerns that water scarcity would threaten agriculture and socio-religious life, underscoring the community’s inseparable relationship with nature. Using a qualitative case study approach, the research draws on online reports, journal articles, and documentary videos to analyze SAPAR’s resistance strategies. Findings reveal that SAPAR operationalizes principles of Islamic environmental ethics, such as khalīfah, amānah, and mīzān, into collective action, framing environmental stewardship as both an ethical and cultural imperative. Religious rituals such as tahlilan and istighosah function as instruments of protest, demonstrating the religious, social, and political engagement. The movement’s discourse reflects a hybridization of Islamic values and local ecological knowledge, challenging dominant “green energy” narratives. This study underscores the need for inclusive policies that prioritize ecological justice and recognize local communities as key actors in sustainable resource governance.